Computational Diversity in the Cochlear Nucleus Angularis of the Barn Owl - Köppl, Christine (2002)
The cochlear nucleus angularis (NA) is widely assumed to form the starting point of a brain stem pathway for processing sound intensity in birds. Details of its function are unclear, however, and its evolutionary origin and relationship to the mammalian cochlear-nucleus complex are obscure. We have carried out extracellular single-unit recordings in the NA of ketamine-anesthetized barn owls. The aim was to re-evaluate the extent of heterogeneity in NA physiology because recent studies of cellular morphology had established several distinct types. Extensive characterization, using tuning curves, phase locking, peristimulus time histograms and rate-level functions for pure tones and noise, revealed five major response types. The most common one was a primary-like pattern that was distinguished from auditory-nerve fibers by showing lower vector strengths of phase locking and/or lower spontaneous rates. Two types of chopper responses were found (chopper-transient and a rare chopper-sustained), as well as onset units. Finally, we routinely encountered a complex response type with a pronounced inhibitory component, similar to the mammalian typeIV. Evidence is presented that this range of response types is representative for birds and that earlier conflicting reports may be due to methodological differences. All five response types defined were similar to well-known types in the mammalian cochlear nucleus. This suggests convergent evolution of neurons specialized for encoding different behaviorally relevant features of the auditory stimulus. It remains to be investigated whether the different response types correlate with morphological types and whether they establish different processing streams in the auditory brain stem of birds.